Foreword: childhood ansd social exclusion - a sociology of the south? - Sarmento, Manuel Jacinto (2020)
The sociology of childhood that developed in the countries of southern Europe, however, always give priority to class differences in the approach to childhood. Issues such as child labor, child poverty, the class character of normative production of childhood, public policies and discrimination against children of popular origin, ill-treatment, migrant children or minority and oppressed ethnic groups have been constituted since always as fundamental in sociological work in several southern countries. Without prejudice to the universalist pretension of scientific work in sociology of childhood, in fact, the combination of social, cultural and epistemological factors operates variations in the production of knowledge between countries or areas of linguistic influence. In this sense, it is perhaps possible to speak of a sociology of southern childhood, characterized by the particular apportion it gives to the scientific field of social studies of childhood.